"To Feel at Home in the Wonderful World of Modern Science": New Chinese Historiography and Qing Intellectual History. Issue 3 (11th October 2017) - Sela, Ori
Argument: In recent decades a large body of scholarship on the first half of twentieth-century China has successfully shown the ways in which history and historiography had been constructed at the time, as well as the links between history, national identity, education, and politics that was forged during this period. In this paper, I examine Qing intellectual history, in particular that of the mid or "High Qing." I discuss the development of the historiography of this field in the early twentieth century by drawing on the larger developments in historiography; by demonstrating how these developments had shaped Qing intellectual history for later times; by focusing on the historical actors' sense of the importance of "science, " being "scientific, " and "modernization"; and, by unraveling the intimate connections to older historiographical narratives going back all the way to the eighteenth and nineteenth centuries.